2019
DOI: 10.3390/nu11092095
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Meat Allergens from Bos taurus β-Lactoglobulin, α-Casein, and Bovine Serum Albumin: An In-Vivo Study of the Immune Response in Mice

Abstract: The mechanism of food allergy may vary. This study aimed to compare the effects of milk, yogurt, or beef meat supplementation on humoral and cellular immune responses in a mice model. Mice were divided into four groups: The “Milk group” was sensitized with a β-lactoglobulin (β-lg)/α-casein (α-CN) mixture and supplemented cow milk; the “Yogurt group” was sensitized with β-lg/α-CN and supplemented yogurt; the “Beef group” was immunized with bovine serum albumin (BSA) and supplemented beef meat; and the “PBS grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…We have reported a beneficial change in the inflammatory pathways of mice that were fed either wild rice or Saskatoon berries [27,28]. Additionally, a recent study monitoring dietary changes in mice demonstrated that specific microbes can alter gut T-cell responses [29]. It is possible that the changes in cytokine concentrations that we observed in wild rice fed LDL-r-KO mice may indirectly influence plasma when phytochemicals produced by altered gut microbiome species reach the blood.…”
Section: Discussionmentioning
confidence: 71%
“…We have reported a beneficial change in the inflammatory pathways of mice that were fed either wild rice or Saskatoon berries [27,28]. Additionally, a recent study monitoring dietary changes in mice demonstrated that specific microbes can alter gut T-cell responses [29]. It is possible that the changes in cytokine concentrations that we observed in wild rice fed LDL-r-KO mice may indirectly influence plasma when phytochemicals produced by altered gut microbiome species reach the blood.…”
Section: Discussionmentioning
confidence: 71%
“…As a stimulation for lymphocytes Con A (10 μg/mL) will be used as a positive control. Cells with no treatment will be considered a negative control [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Purified spleen lymphocytes (SPLs) were cultured in 96-well plates (1 × 10 6 /well) with 200 µL of the complete medium (CM: RPMI 1640 containing 10% heat-inactivated fetal bovine serum, 1 mM non-essential amino acid, 1mM sodium pyruvate, 1mM HEPES, and 10 units/mL penicillin–streptomycin) and then incubated for 120 h, at 37 °C and 5% CO 2 , in the presence of either concanavalin A (ConA, positive control) (10 µg/mL) or OVA (100 µg/mL). The supernatants were collected and stored at −80 °C until analysis, and lymphocytes were harvested for phenotyping by flow cytometry [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance was measured at 405 nm on a Jupiter UVM spectrophotometer (ASYS-Hitech GmbH, Eugendorf, Austria). The endpoint titers (EPTs) were expressed as the reciprocal dilution of the last sample dilution of 0.1 OD above the negative control [ 42 , 43 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%